Om Engculturen. (Udvalgte Afsnit af "Der praktische Rieselwirth," Leipzig 1840.) - Patzig, H. C. (Tidsskrift for Landøkonomi, 2018)
Om Engculturen. (Udvalgte Afsnit af "Der praktische Rieselwirth," Leipzig 1840.)